2021
DOI: 10.1002/app.50849
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous carbon derived from green cyclodextrin metal‐organic framework and its application in microwave absorption

Abstract: γ‐cyclodextrin (CD)‐metal‐organic framework (MOF)‐K is developed as a new kind of green template for the preparation of hierarchical porous carbon (HPC). Three‐level porous structure (micro‐, meso‐, and macro‐pores) has been successful constructed by calcined γ‐CD‐MOF‐K at 600°C. The fabricated carbon (HPC‐600) shows good microwave adsorption ability due to its unique hierarchical porous structure (macropores allow microwave enter the interior of the absorbents, and then micro‐ and meso‐pores attenuate the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Furthermore, different pore sizes correspond to different microwave length, which indicates that the gradient distribution of pore structure is beneficial to broaden the EAB [ 149 ]. Besides, macropores can facilitate the impedance match of MAMs, while mesopores and micropores can enhance the multiple reflection of microwave inside the MAMs [ 109 ]. There are many approaches to construct MAMs with multiple pore sizes such as etching [ 176 ] and template method [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, different pore sizes correspond to different microwave length, which indicates that the gradient distribution of pore structure is beneficial to broaden the EAB [ 149 ]. Besides, macropores can facilitate the impedance match of MAMs, while mesopores and micropores can enhance the multiple reflection of microwave inside the MAMs [ 109 ]. There are many approaches to construct MAMs with multiple pore sizes such as etching [ 176 ] and template method [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al fabricated ingenious hierarchical porous carbon (HPC) materials using γ-CD-MOF-K as carbonizing template with K 2+ acted as activator in the formation of HPC (Fig. 8 g) [ 109 ]. The HPC-600 was obtained by directly pyrolyzing γ-CD-MOF-k at 600 °C, and the HPC-600-900 was fabricated by calcining HPC-600 at 900 °C subsequently.…”
Section: Mams Derived From Mofsmentioning
confidence: 99%
“…The few compounds synthesized until now have shown auspicious performance in isomer separation, agriculture, watertreatment, and microwave absorption. [69][70][71]172 3.3.1 Synthesis CD-MOF derived materials. The most common and important compounds derived from CD-MOFs are nanoporous carbon (NPC) materials.…”
Section: Cd-mof Derived Materialsmentioning
confidence: 99%
“…Interestingly, it was found that the unique hierarchical structure of g-CD-MOF derived HPC endows it with microwave absorption abilities. 172 At first, the large number of macro-pores allows the electromagnetic waves to enter the interior of the structure due to the good impedance matching of the material. Then, the incident microwave can be effectively attenuated by multiple reflections and polarization loss in the micro-and meso-pores.…”
Section: Cd-mof Derived Materialsmentioning
confidence: 99%
See 1 more Smart Citation